Exploring the molecular basis of action of ring D aromatic steroidal antiestrogens - Alvarez, Lautaro Damian (2015)
Salpichrolides are natural plant steroids that contain an unusual six-membered aromatic ring D. We recently reported that some of these compounds, and certain analogs with a simplified side chain, exhibited antagonist effects toward the human estrogen receptor (ER), a nuclear receptor whose endogenous ligand has an aromatic A ring (estradiol). Drugs acting through the inhibition or modulation of ERs are frequently used as a hormonal therapy for ER(+) breast cancer. Previous results suggested that the aromatic D ring was a key structural motif for the observed activity; thus, this modified steroid nucleus may provide a new scaffold for the design of novel antiestrogens. Using molecular dynamics (MD) simulation we have modeled the binding mode of the natural salpichrolide A and a synthetic analog with an aromatic D ring within the ERα. These results taken together with the calculated energetic contributions associated to the different ligand-binding modes are consistent with a preferred inverted orientation of the steroids in the ligand-binding pocket with the aromatic ring D occupying a position similar to that observed for the A ring of estradiol. Major changes in both dynamical behavior and global positioning of H11 caused by the loss of the ligand–His524 interaction might explain, at least in part, the molecular basis of the antagonism exhibited by these compounds. Using steered MD we also found a putative unbinding pathway for the steroidal ligands through a cavity formed by residues in H3, H7, and H11, which requires only minor changes in the overall receptor conformation.